The impact of pulmonary tuberculosis on immunological and metabolic features of diabetic patients - Chen, Haijun; Su, Li; Bao, Jinhua; Zhang, Kun; Li, Yuze; Mao, Enuo (Frontiers in Immunology, 2022)
The impaired immune response has been demonstrated in patients with type-2 diabetes mellitus (T2DM), which poses them susceptibility for tuberculosis infection. However, how tuberculosis infection affects immunological and metabolic features of T2DM is not well defined. To investigate this question, age- and gender-matched patients with pulmonary tuberculosis (PB), T2DM, or T2DM combined with PB were recruited from Infectious Disease Hospital of Heilongjiang Province from January to September 2020. T2DM patients. Healthy subjects were included as controls. Cytokines and chemokines were determined by Quantibody Inflammation Array in fasting serum samples. Compared with T2DM alone, T2DM combined with PB patients have higher fasting blood glucose levels and monocyte count in the circulation. Among four groups, circulating IL-10 levels were peaked in T2DM plus PB patients (p<0.05). By univariate linear analysis, serum IL-10 levels were positively associated with myeloid cells but negative related to lymphocyte count in the patients (p<0.05). Serum IL-6 levels were 1.6-fold increase in T2DM plus PB patients compared with T2DM alone. In conclusion, TB infection in T2DM patients had distinct inflammatory profiles and sustained hyperglycemia in comparison to TB or T2DM alone. IL-10 levels and elevated monocyte count could be hallmarks in T2DM patients infected with TB.